Characteristics of temper tantrums in 1–6-year-old children and impact on caregivers - Warangkana Prutipaisan; Issarapa Chunsuwan; Tippawan Hansakunachai; Paskorn Sritipsukho (Clinical and Experimental Pediatrics)
Background Temper tantrums are common behavioral difficulties in children. Although they are generally considered a normal part of development, certain characteristics— such as aggression, prolonged duration, and frequent occurrences—have been linked to psychological issues and can negatively impact both the child and their caregivers. Purpose To study the prevalence and characteristics of temper tantrums in children aged 1–6 years at daycare and in kindergarten in Thailand as well as the impact of problematic and nonproblematic tantrums on their caregivers’ emotional well-being. Methods This cross-sectional descriptive study was conducted in 2021. The main caregivers of the participants completed self-reported questionnaires that collected their demographic information and the temper tantrum characteristics and impacts on the caregivers’ emotions. Results Data from 211 children were included in this study. The mean child age was 4.4±1.2 years. Two hundred one parents (95.3%) reported that their children had at least one tantrum behavior, of which verbal were the most common (94.5%). One hundred and 11 children (55.2%) had tantrums defined as problematic: exhibiting aggressive physical behavior, duration >15 minutes, frequency >3 days/wk. The mean emotional burden scores of the children’s problematic and nonproblematic temper tantrums on their parents were 23.3±8.4 and 17.7±8.3 (maximum, 55; P=0.001), respectively, showing a statistically significant difference. Conclusion Tantrums are common in children aged 1–6 years, but their expression varies. Problematic tantrums were reported for approximately half of the children and significantly impacted their caregivers’ emotions. Therefore, children with problematic tantrums and their families should receive assistance.